The Supremacy of Authority: Its Impact and Barriers on Content Development - Sahakyan, Hayarpi (Bulletin of Yerevan University E: Philosophy, Psychology, 2025)
The article explores the phenomenon of the cult of authority and itsimpact on the objective evaluation of content, the dissemination of innovation, and societal progress. Thisissue is examined within various historical and cultural contexts, highlighting how positions of authorityoften become tools for the dominance of ideas, overshadowing the true value of the content itself. Authorityserves not only as a source of influence but also as a mechanism for shaping social norms and value systems,potentially hindering free and critical thinking. The analysis draws on the perspectives of Michel Foucault,Roland Barthes, Karl Popper, and Edward Said, who emphasize the promotion of free thought and criticalapproaches. Foucault examines mechanisms of control and how they restrict intellectual freedom. Barthes,through his concept of the "death of the author," advocates for focusing on the content itself, irrespective ofits creator. Karl Popper underscores the importance of openness in scientific thought and the necessity ofcritical discussion, while Said, through his analysis of East-West binary oppositions, reveals culturalhierarchies shaped by authority. These issues, in turn, point to the challenges of intellectual freedom, the openexchange of ideas, and hierarchies within cultural institutions. It concludes that the liberalization ofeducational and cultural systems could lead to the recognition and appreciation of the intrinsic value ofcontent. Ultimately, creating environments free from the influence of authority is essential for fosteringinnovation, promoting inclusivity, and advancing societal progress by ensuring the development of free andcritical thinking.
Keywords: authority bias; author; content; text; reader; perception; author function; critical thinking; scriptor; Roland Barthes; Karl Popper; Edward Said; Michel Foucault